P1 Receptor Agonists/Antagonists in Clinical Trials - Potential Drug Candidates of the Future - Borah, Pobitra; Deka, Satyendra; Mailavaram, Raghu P.; Deb, Pran Kishore (Current Pharmaceutical Design, 2019)
Background: Adenosine mediates various physiological and pathological conditions by acting on its four P1 receptors (A1, A2A, A2B and A3 receptors). Omnipresence of P1 receptors and their activation, exert a wide range of biological activities. Thus, its modulation is implicated in various disorders like Parkinson’s disease, asthma, cardiovascular disorders, cancer etc. Hence these receptors have become an interesting target for the researchers to develop potential therapeutic agents. Number of molecules were designed and developed in the past few years and evaluated for their efficacy in various disease conditions. Objective: The main objective is to provide an overview of new chemical entities which have crossed preclinical studies and reached clinical trials stage following their current status and future prospective. Methods: In this review we discuss current status of the drug candidates which have undergone clinical trials and their prospects. Results: Many chemical entities targeting various subtypes of P1 receptors are patented; twenty of them have crossed preclinical studies and reached clinical trials stage. Two of them viz adenosine and regadenoson are approved by the Food and Drug Administration. Conclusion: This review is an attempt to highlight the current status, progress and probable future of P1 receptor ligands which are under clinical trials as promising novel therapeutic agents and the direction in which research should proceed with a view to come out with novel therapeutic agents.
Keywords: P1-receptors